La compresión lectora en el inter - aprendizaje de los estudiantes del sexto y séptimo año de Educación General Básica de la Escuela Rodrigo Riofrío Jiménez" del cantón San Miguel- provincia Bolívar, durante el año lectivo 2010 - 2011 - Nájera Sosa, Rubén Darío (2011)
Reading comprehension is the process of making meaning by way of learning the relevant ideas of a text and relate them to ideas they already have. It is the process through which the reader will "interact" with the text. No matter the length or brevity of the paragraph, the process is prevented, always in the same way, never given. Reading is a process of interaction between thought and language, the reader needs to recognize letters, words, phrases, however when reading does not always understand the message contained in the text, our mentality is not enough for both honestly, it is even possible to misunderstand, as almost always happens. As intellectual ability, understanding involves capturing the meanings that others have passed through sounds, images, colors and movements. Reading comprehension is a more complex process to identify words and meanings, this is the difference between reading and understanding. Understanding is then closely linked with the vision that everyone has the world and of himself, therefore, with the same text, we can not expect a unique interpretation and objective. Reading is a process of interaction between reader and text, the process by which the former attempts to meet the goals that guide their reading, the text's meaning is constructed by the reader. This does not mean that the text itself does not make sense or meaning, the meaning that a letter is for the reader is not a translation or replication of the meaning the author wanted to impart, but a construction that involves the text to background the reader who approaches and objectives facing thereto. ' The reader will give meaning to read coordinate information from different sources: the text, its context and the knowledge he possesses. To meet this goal successfully, the reader must use a set of skills or strategies to help you build your knowledge, applying them in different situations and different contexts. Our role as teachers to accompany students to move this process will then be: Teaching reading comprehension strategies, providing them with the resources needed to learn to learn, acquire skills that will tend to the development of operations as the recognition and prioritization of ideas, summarization, analysis of text information and the relationship and comparison with prior knowledge, formulating hypotheses, issuing opinions, the relationship between text and image. All these skills will be linked to levels of reading comprehension. In Chapter I, is a thorough review of the topics that allows the support of the hypothesis, the arguments and theories raised verification on the subject under investigation. In Chapter II, the proposed methodology presented in this paper, as data collection instruments used primary and secondary sources (surveys). The population under investigation consisted of 66 persons, of whom 20 are teachers who work at school and 46 students in the Sixth and Seventh Year of General Basic Education. The other went to a major methodological field and properly selected, the characteristics addressed include the descriptive, explanatory, transversal and comparative methods over the deductive-inductive, analogical comparison, verbalístico symbolic and descriptive, which contributed in the search for truth. In Chapter III, we discuss the analysis, discussion of the results obtained during implementation of the survey and research work, on skills to improve reading comprehension, the change implemented by applying tools and instruments, finally conclusions and recommendations that will enhance the success, progress and development of knowledge of students. Chapter IV. They pose an alternative solution to the problem through a viable and novel proposal with a tutorial of methods and techniques to encourage active reading.